Problematika pembelajaran tematik kelas v sd angkasa lanud adi soemarmo pasca pandemi - Azzahra, Daffa; Marmoah, Sri; karsono, Karsono (Didaktika Dwija Indria, 2025)
This study aims to describe the problematic implementation of thematic learning for fifth grade students at SD Angkasa Lanud Adi Soemarmo after the pandemic. This research is a qualitative study that uses data collection techniques through observation, interviews, and documentation. The subjects of this study were 10 fifth grade students of SD Angkasa Lanud Adi Soemarmo. The data validity technique applied was triangulation of techniques between observation, interviews, and documentation. Miles and Huberman's interactive analysis model was used as the data analysis technique of this research. The results of the study show that the problems that occur during the implementation of thematic learning in class V students are less than optimal classroom management, mastery of material when teaching, the absence of learning assessment, differences in the level of understanding of students, lack of involvement and enthusiasm of students, and lack of facilities and infrastructure that are inadequate in the classroom.